2021
DOI: 10.1371/journal.pone.0248274
|View full text |Cite
|
Sign up to set email alerts
|

De novo genome assembly of Bacillus altitudinis 19RS3 and Bacillus altitudinis T5S-T4, two plant growth-promoting bacteria isolated from Ilex paraguariensis St. Hil. (yerba mate)

Abstract: Plant growth-promoting bacteria (PGPB) are a heterogeneous group of bacteria that can exert beneficial effects on plant growth directly or indirectly by different mechanisms. PGPB-based inoculant formulation has been used to replace chemical fertilizers and pesticides. In our previous studies, two endophytic endospore-forming bacteria identified as Bacillus altitudinis were isolated from roots of Ilex paraguariensis St. Hil. seedlings and selected for their plant growth-promoting (PGP) properties shown in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Among all strains, Bacillus zanthoxyli and Bacillus altitudinis were the most potent in promoting tall fescue growth under salt condition on account of their better tolerance to salt, their fast growth rate in the salt environment, IAA secreting ability, phosphorus dissolving ability, and potassium dissolving ability. Several reports are in agreement with our results regarding their effectiveness as PGPR (Cortese et al, 2021; Khan et al, 2019). For instance, it is reported that Bacillus altitudinis reduces low‐phosphorus stress and high‐salinity stress in wheat by producing soluble phosphatases and phytases (Yue et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Among all strains, Bacillus zanthoxyli and Bacillus altitudinis were the most potent in promoting tall fescue growth under salt condition on account of their better tolerance to salt, their fast growth rate in the salt environment, IAA secreting ability, phosphorus dissolving ability, and potassium dissolving ability. Several reports are in agreement with our results regarding their effectiveness as PGPR (Cortese et al, 2021; Khan et al, 2019). For instance, it is reported that Bacillus altitudinis reduces low‐phosphorus stress and high‐salinity stress in wheat by producing soluble phosphatases and phytases (Yue et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…B. altitudinis was first isolated from extreme UV-stressed air samples collected in the stratosphere [73]. It has been identified as an endophyte in various plants, including soybean [74] and others [75, 76, 77, 78, 79, 80, 81]. Several strains of B. altitudinis have shown biocontrol capabilities, such as cotton Verticillium wilt [75], grape downy mildew [78], kiwi fruit root-knot nematodes [82], soybean Phytophthora damping-off [74] and sweet potato black rot [80].…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic sequencing datasets obtained from ENA public database and in-house metagenomic sequencing data were quality filtered by using trimmomatic v_0.33 software to remove low quality sequences [15]. Human sequences were removed after alignment with a reference genome (hg38 database) using Bowtie2 v_2.2.4, with default settings [16].…”
Section: Methodsmentioning
confidence: 99%